Zonal Management: addressing sustainability issues in aquaculture - Morales, Ernesto J; Immink, Anton; Pamudi, Pamudi; Thanh, Linh Nguyen; Han, H (Indonesian Aquaculture Society (MAI), 2017)
Aquaculture industries in general face several sustainability issues as the operations still rely on the quality of available water resources. Most aquaculture systems utilize common water resources in the production as well as discharging effluents from the farm; hence water is still considered as the major factor in spreading diseases in an area where aquaculture production is concentrated. Moreover, most input sources (e.g feeds, seeds and chemicals) in most cases are also similar (or shared) among aquaculture producers in the area. The most common recommended best management practices nowadays, including those from the national and commercial aquaculture standards, limit the requirements in addressing management issues that can be controlled within the farm only and that the outside environment (e.g. rivers and coastal areas) in most cases is overlooked. Producers are commonly advised to improve their individual practices in order to achieve higher production and limiting the occurrence of disease within the farm. The Sustainable Fisheries Partnership (SFP) as an organization that promotes sustainable practices in fisheries and farming, recognizing the cumulative impact of aquaculture on receiving water bodies where aquaculture production is pooled and intensified. Due to the minimal (if not lacking) regulations and coordination among producers on the use of water resources and effluent discharge, sourcing inputs, stocking events, reporting of disease outbreak and the use of drugs and chemicals, the fate of aquaculture as a whole is uncertain. This paper introduces the five pillars of zonal management where scientific information (carrying capacity and epidemiology) are critical as well as the laws and regulations in order to develop better management recommendations that would cover an aquaculture zone. Moreover, this paper provides updates on the different approaches applied in aquaculture zones in China, Indonesia and Thailand in pursuit to a more sustainable practice in aquaculture through zonal management. The approach uses a multi-stakeholder strategy where key players of the aquaculture industry play a critical role. The paper highlights that there is no strategy that would fit in all aquaculture zones rather would mainly depend on the status of the industry, hence the level of importance and the role that each stakeholder plays may not be the same in all zones.